2020
DOI: 10.2147/nss.s254473
|View full text |Cite
|
Sign up to set email alerts
|

<p>Does Nasal Obstruction Induce Obstructive Sleep Apnea in Healthy Women?</p>

Abstract: Purpose: Obstructive sleep apnea (OSA) is less prevalent among women and is associated with different symptoms and consequences to OSA in men. The reasons for these differences are unknown and difficult to tease apart in clinical populations. If OSA could be temporarily induced in healthy men and women, the causes of some of these differences could be investigated. Nasal blocking has been used to induce OSA in healthy men but its effect in women has not been reported. Patients and Methods: A total of 14 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In people with OSA, nasal obstruction is a common problem. Research conducted by Pittaway et al reported that nasal obstruction in healthy young adult women could cause OSA [10]. Sianturi et al, in their research, found a significant relationship between OSA and allergic rhinitis (p = 0.000) [11].…”
Section: Introductionmentioning
confidence: 91%
“…In people with OSA, nasal obstruction is a common problem. Research conducted by Pittaway et al reported that nasal obstruction in healthy young adult women could cause OSA [10]. Sianturi et al, in their research, found a significant relationship between OSA and allergic rhinitis (p = 0.000) [11].…”
Section: Introductionmentioning
confidence: 91%